Représenter la représentation : les assemblées de l’Antiquité, miroirs de la Révolution à la scène - Éric Avocat (Revue Italienne d'Etudes Françaises)
The presence of Antiquity in the political imagination of the Revolution found a powerful vector on the theatre stage, where Greek and Roman subjects resonated with the exaltation of patriotic and republican heroism. They were also in touch with the major event of the emergence of parliamentary assemblies, which the spectating public perceived and judged more acutely through the prism of the stage. However, if the dramatic creations of the period focus on the people’s assemblies and oligarchic senates that made up the history of Rome and Greece, rather than modern or contemporary assemblies, it is also because they re-enact the ups and downs of the birth of representative institutions and respond to the feeling of fragility that haunted the revolutionary actors in the face of their political work.